Thinking Berikut adalah judul yang telah diperbaiki agar terbaca dengan benar: Tess’ Fateful Life in Thomas Hardy’s Tess of the D’Urbervilles - Sufi Ikrima Saadah (Tell : Teaching of English Language and Literature Journal, 2017)
This article aims to explore the work of fate in the sense of natural law and its manifestation in leading the life of the heroine in Thomas Hardy's Tess of the D'Urbervilles. The theoretical framework is the concept of fate and Sartre's Existentialism by applying the concept of free will and personal responsibility. The analysis focuses on any natural events that happen in Tess' life, which eventually become such fate agents in determining Tess' life. The finding says that no matter how fateful her life is, Tess exhibits how much she stands on her own by revealing her own free will and her personal responsibility regarding her reaction towards the fateful events she undergoes.